2018
DOI: 10.1038/s41405-018-0006-4
|View full text |Cite
|
Sign up to set email alerts
|

Experience with bruxism in the everyday oral implantology practice in the Netherlands: a qualitative study

Abstract: ObjectiveTo explore how bruxism is dealt with by accredited oral implantologists within daily clinical practice.Materials and methodsNine semi-structured interviews of oral implantologists practicing in non-academic clinical practices in the Netherlands were performed, and thematic analysis was conducted using a framework-based approach.ResultsOral implant treatments in bruxing patients were a generally well-accepted practice. Complications were often expected, with most being of minor impact. Contradictive at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Occlusal splints are recommended by clinicians in the case that sleep bruxism is suspected, for example due to a history of severe dental attrition or repeated fractures of dental restorations. 26 Thus, by using this as an exclusion criterion, it is possible that a high-risk group of bruxers is filtered out from the study sample, consequently biasing study outcomes. As shown in the retrospective study by Chrcanovic et al, "possible" and "probable" sleep and/or awake bruxism may be associated with an increased risk of dental implant failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Occlusal splints are recommended by clinicians in the case that sleep bruxism is suspected, for example due to a history of severe dental attrition or repeated fractures of dental restorations. 26 Thus, by using this as an exclusion criterion, it is possible that a high-risk group of bruxers is filtered out from the study sample, consequently biasing study outcomes. As shown in the retrospective study by Chrcanovic et al, "possible" and "probable" sleep and/or awake bruxism may be associated with an increased risk of dental implant failure.…”
Section: Discussionmentioning
confidence: 99%
“…16 Moreover, careful selection of variables is also important considering that a large number of such variables can increase the risk for type I error. Given the significant number of variables that can be assessed in a bruxism-dental implant complication study (e.g., 27 ), it is suggested that future studies in the field include at least a set of 'classic' confounders/covariates, i.e., smoking and periodontal parameters, variables emerging from clinical studies (e.g., 27 ), and variables emerging from the experience of dentists in daily practice (e.g., 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…The assessment of bruxism based on intra-and extraoral clinical signs has also been described in other practicebased studies. 3,4 Recently, the BruxScreen pre sented a brief tool for the standardized assessment of extraand intraoral signs that may be associated with bruxism. 12 Alongside the clinical signs that are assessed in the BruxScreen, the results of the present study provide suggestions for the development of a comprehensive instrument for the wider assessment of clinical signs of sleep and awake bruxism in future versions of the STAB.…”
Section: Clinical Examinationmentioning
confidence: 99%
“…1,2 Clinicians usually base their bruxism assessments on self-reports and/or clinical examination. 3,4 Ideally, bruxism assessments in the clinic should be based on standardized tools. 5 The Standardized Tool for the Assessment of Bruxism (STAB) is a crucial part of the successful implementation of the bruxism diagnostic grading system, 5 allowing for consistent assessments in clinical practice and research.…”
Section: Introductionmentioning
confidence: 99%
“…The development of an ideal assessment tool remains of high priority in the sleep bruxism research agenda . Patient self‐report and/or clinical examination are extensively used . These methods are simple, low cost and readily available, but unfortunately lack validity .…”
Section: Introductionmentioning
confidence: 99%